Criminal Legal Aspects Of The Use Of Artificial Intelligence (AI) As A Means Of Fraud From The Perspective Of ITE Law - Rudi Salam Tarigan; Mhd. Azhali Siregar; Rahmayanti , Rahmayanti (PT. Sinergi Legal Publisher, 2025)
The rapid development of information and communication technology has brought about various innovations, one of which is artificial intelligence (AI). However, despite its benefits, AI also has the potential to be misused as a means to commit crimes, particularly digital fraud. This study aims to analyze the criminal law aspects of the use of AI as a tool for fraud crimes from the perspective of the Electronic Information and Transactions Law (UU ITE). The method used is a normative juridical approach by reviewing relevant laws and regulations, legal literature, and case studies. The results of the study indicate that although the ITE Law does not explicitly regulate the use of AI, criminal provisions in articles related to electronic fraud can be applied to perpetrators who use AI to defraud. Furthermore, there is an urgency for policymakers to formulate more comprehensive regulations to anticipate AI-based digital crimes. This study recommends the need for national legal updates that are adaptive to technological advances, as well as increasing the capacity of law enforcement officials in detecting and handling cybercrimes involving AI